Natural products as a source of cytotoxic warheads in antibody-drug conjugates - Goel B.; Jain S.K. (My University, 2025)
Antibody-drug conjugates (ADCs) are one of the most rapidly expanding classes of oncology therapeutics. Till now, 11 ADCs have been approved by USFDA, with the first ADC approval of gemtuzumab ozogamicin (Mylotarg) in 2000. A large number of ADCs are being evaluated in different stages of clinical trials and pre-clinical studies. Interestingly, the cytotoxic warheads of the all approved ADCs, as well as clinical and preclinical candidates, belong to different classes of natural products viz. calicheamicins, auristatins, maytansinoids, camptothecin derivatives, pyrolidobenzodiazepines (PBDs), and duocarmycins, etc. Herein, a review of the natural product-based cytotoxic warheads, briefly discussing their source, modifications, and mechanism of action, has been conducted. © 2022 Informa UK Limited, trading as Taylor & Francis Group.